LATE ONSET PSYCHOSIS IN THE ELDERLY: DIFFERENTIAL DIAGNOSIS AND THE IMPACT OF BRAIN AGING - Djosci Coêlho de Sá, Henrique; Julia Milholo Robles, Ana; Costa de Mello Farah, Vinicius; Fernandes Alevato, Lucca; Víctor Elias Sobrinho, Paulo; Andre Ramalho Rangel Lima, Paulo; Sérgio Martins Neto, José; Bandeira de Mello Sanches de Almeida, Eduardo; Hugo Mendes da Cunha, Vitor; Zanetti Pinheiro, Thiago; Vitor Gullo de Oliveira Ribeiro, Antônio; Tibério Campos Calegário, Luiza (Health and Society, 2024)
Late-onset psychosis in the elderly is a condition characterized by the onset of psychotic symptoms, such as hallucinations and delusions, after the age of 60. Although psychosis at younger ages is often associated with primary psychiatric disorders such as schizophrenia, diagnosis in the elderly is more complex, as it involves the need to differentiate between various conditions that can affect the brain and behavior, such as dementias, neurological disorders and factors related to brain aging. The impact of brain aging, such as diminished cognitive abilities and changes in brain structure, also plays an important role in the development and course of psychosis in this age group. The aim of this work is to analyze the differential diagnosis of late onset psychosis in the elderly, exploring the conditions that can mimic psychotic symptoms and the impact of brain aging on this process. It also aims to assess the implications of this diagnosis for clinical management and patients’ quality of life. This study uses a systematic review to investigate late onset psychosis in the elderly, its relationship with neurodegenerative diseases, differential diagnoses with dementias and therapeutic approaches, both pharmacological and non-pharmacological. The search was carried out in databases such as SciELO, PubMed, LILACS and Journal of Neurosciences, and included analysis of critical reviews, empirical studies and clinical guidelines. Additional data was obtained from population studies and clinical analyses involving geriatric patients with psychosis. The differential diagnosis of late onset psychosis is challenging, as it involves distinguishing between primary and secondary psychiatric causes. Neurodegenerative disorders, such as Alzheimer’s disease and dementia with Lewy bodies, are often associated with psychotic symptoms in the elderly. Likewise, disorders such as major depression with psychotic features and delirium can present with similar symptoms, and a detailed clinical assessment is essential. The exclusion of underlying medical factors, such as infections, metabolic disorders and adverse effects of medication, is crucial to ensure an accurate diagnosis. Brain aging, in turn, plays a key role in the vulnerability of the elderly to psychosis. With age, structural and functional changes occur in the brain, such as cortical atrophy, reduced neuronal density and alterations in dopaminergic pathways, which can predispose to the emergence of psychotic symptoms. These changes make the brain more susceptible to stress factors, inflammation and sensory deficits, which can precipitate psychotic episodes. Thus, the treatment of late onset psychosis involves a careful approach, given the sensitivity of the elderly to antipsychotics and the increased risk of side effects. The choice of treatment must balance efficacy in controlling symptoms with minimizing risks, and the use of low doses and constant monitoring are recommended to avoid complications. It is therefore concluded that late onset psychosis in the elderly presents significant diagnostic challenges, requiring a multifactorial approach that takes into account brain aging and the various medical conditions that can mimic or contribute to psychotic symptoms. Differential diagnosis is essential to ensure appropriate treatment, which, when properly targeted, can substantially improve patients’ quality of life. The impact of brain ageing on vulnerability to psychosis highlights the need for detailed clinical assessment and individualized therapeutic strategies for this population group.